Towards a better risk stratification for sudden cardiac death in patients with structural heart disease - Kraaier, K. (Bohn Stafleu van Loghum, 2009)
With the introduction of the implantable cardioverter defibrillator (ICD), patients can be protected against sudden cardiac death (SCD) due to ventricular arrhythmia (VA). Guidelines have been drawn up for selecting patients for primary and secondary prophylaxis. However, most ICD recipients today who receive an ICD for primary prevention will not experience a life-threatening VA requiring antitachypacing or shock therapy. Better risk stratification is desirable with efficacy, costs and complication rate in mind. An overview is presented of widely accepted and potentially valuable risk markers and the role they may play in better identifying candidates for ICD therapy. (Neth Heart J 2009;17:101-6.)